The Role of Tourist Ambassadors in the Image Establishment of Palu City After the Natural Disasters through Instagram - Sumarni Zaenuddin; Donal Adrian (2020)
The purpose of research is to know the role of tourist ambassadors in the formation of the image of Palu City after the natural disasters through Instagram. The method used is qualitative with a case study approach withdrawal of informant using purposive sampling. Research findings show that in the effort to build imagery through Instagram, the main thing that is done by tourist ambassadors (Randa'a ante Kabilasa) is by changing the perception of society as a follower through the publication of various kinds of information/content both in the form of images, texts, and videos about the city of Palu affected by natural disasters but able to rise to a better change, i.e. the activity of public that return to normal in the field of economics and culture. Furthermore, the improvement of land road infrastructure, air (airport) and the sea (port) is the main focus of the government.Ã‚Â